Status of Trichoderma research in India: A review - M. RAJA; V. SHANMUGAM, PRATIBHA SHARMA*, M. SHARMA (Indian Phytopathology, 2014)
Species of Trichoderma are diverse fungal microbial community known and explored worldwide for their versatilities as biocontrol and growth promoting agents. They are also widely exploited in industries as sources of enzymes. A large number of research groups are working on various aspects of Trichoderma viz., diversity, ecology and their applications. In India, about 110 groups representing various universities and research institutes are working with about 15 different species and have published about 460 research papers. Trichoderma harzianum and Trichoderma viride are the widely used species and have been exploited on about 87 different crops and about 70 soilborne and 18 foliar pathogens, respectively. This review aims to give an overview of the status of usage of Trichoderma on important agricultural crops by different groups and organizations in the country.